Technical effectiveness of cement-based mortar for high-reflective building envelope through building energy simulations: preliminary results - Alessandra Gugliandolo; Enrico Genova; Francesco Baldi; Claudia Capone; Maria Anna Segreto (Acta Polytechnica CTU Proceedings)
In areas with high levels of solar radiation, decreasing the amount of solar energy absorbed by the building envelope is useful to reduce the need of air conditioning and "heat island" effects. Most high-reflective products, however, suffer from low durability. The COOL-IT project is developing an innovative high-reflective cement based mortar for precast products to be used as outer layer in buildings for both vertical and horizontal surfaces, or for road pavement. The mix design is aimed at increasing the durability of this cement-based component while retaining high reflectance to solar radiation. This paper presents the preliminary results of the project, based on the simulation of the energy demand of a residential building, intended as a support to optimize the proposed mixes. The model is analysed in three different locations in Italy, for one year of operation. This allows evaluating the trade-off of the energy demand between the winter increase and the summer reduction.